The Type 9 Secretion System Is Required for Flavobacterium johnsoniae Biofilm Formation - Eckroat, Todd J.; Greguske, Camillus; Hunnicutt, David W. (Frontiers in Microbiology, 2021)
Flavobacterium johnsoniae forms biofilms in low nutrient conditions. Protein secretion and cell motility may have roles in biofilm formation. The F. johnsoniae type IX secretion system (T9SS) is important for both secretion and motility. To determine the roles of each process in biofilm formation, mutants defective in secretion, in motility, or in both processes were tested for their effects on biofilm production using a crystal violet microplate assay. All mutants that lacked both motility and T9SS-mediated secretion failed to produce biofilms. A porV deletion mutant, which was severely defective for secretion, but was competent for motility, also produced negligible biofilm. In contrast, mutants that retained secretion but had defects in gliding formed biofilms. An sprB mutant that is severely but incompletely defective in gliding but retains a fully functional T9SSs, was similar to the wild type in biofilm formation. Mutants with truncations of the gldJ gene that compromise motility but not secretion showed partial reduction in biofilm formation compared to wild type. Unlike the sprB mutant, these gldJ truncation mutants were essentially nonmotile. The results show that a functional T9SS is required for biofilm formation. Gliding motility, while not required for biofilm formation, also appears to contribute to formation of a robust biofilm